1999
DOI: 10.1159/000016938
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inflammatory Bowel Disease on Health-Related Quality of Life

Abstract: Health-related quality of life (HRQOL) has a recognized importance to evaluate, manage and follow patients. Different types of instruments for measuring HRQOL have recently been introduced to evaluate HRQOL in patients with inflammatory bowel disease. Most questionnaires suggest that inflammatory bowel disease has a significant impact in HRQOL. It seems that ulcerative colitis has less profound effects on HRQOL than Crohn’s disease and that some differences in HRQOL status are related to some factors such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
1
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 47 publications
1
71
1
6
Order By: Relevance
“…Nonetheless, Kasman et al found that female patients younger than 65 years old, white, with low income and having completed secondary school more frequently reported dissatisfaction with healthcare services (9). The differences between this and our study could be explained by the study population as Kasman reported results from a population based study including healthy people as well as ill patients for whom the use of healthcare resources might not be as high as it is for IBD patients (7).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Nonetheless, Kasman et al found that female patients younger than 65 years old, white, with low income and having completed secondary school more frequently reported dissatisfaction with healthcare services (9). The differences between this and our study could be explained by the study population as Kasman reported results from a population based study including healthy people as well as ill patients for whom the use of healthcare resources might not be as high as it is for IBD patients (7).…”
Section: Discussioncontrasting
confidence: 68%
“…IBD is a chronic illness with an intense impact on patients' Health Related Quality of Life (HRQOL) and is associated with a high level of healthcare resource consumption (6,7). Also the patient satisfaction with the healthcare services has been seen to be related to the clinical outcomes in patients with chronic illness (3).…”
Section: Discussionmentioning
confidence: 99%
“…Por ello, el campo de la calidad de vida relacionada con la salud (CVRS) ha ganado protagonismo en la medicina y especialmente en la gastroenterología. Este interés es reflejado en el factor que el sujeto es regularmente citado en la literatura médica (1).…”
Section: Introductionunclassified
“…The questionnaire consisted of closed questions, chosen on the basis of personal clinical experiences, as well as data from the literature [6][7][8][9]; there were three possible answers to the questions: "yes", "no" and "don't know". The questions were arranged in such a way as to eliminate the suggestion component, as well as the so-called inner control.…”
Section: Methodsmentioning
confidence: 99%